2018
DOI: 10.2967/jnumed.117.200220
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Comparison of 99mTc-Methylene Diphosphonate and Prostate-Specific Membrane Antigen Ligand 99mTc-MIP-1427 in Patients with Osseous Metastasized Prostate Cancer

Abstract: The objective of this study was to evaluate the rate of detection of bone metastases obtained with the prostate-specific membrane antigen (PSMA)-targeting tracer Tc-MIP-1427, as opposed to conventional bone scanning withTc-methylene diphosphonate (Tc-MDP), in a collective of patients with known advanced-stage osseous metastasized prostate cancer. Twenty-one patients with known metastatic disease were staged with both conventional bone scanning and PSMA ligand scintigraphy within a time frame of less than 10 d.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 32 publications
2
32
0
1
Order By: Relevance
“…In order to determine the binding affinity of both conjugates, we carried out the chemical synthesis of MIP-1427, a 99m Tc-radiolabeled, well-established PSMA-targeting imaging probe which has already been evaluated in patients. 32 , 50 Following successful synthesis, we carried out a radioactive displacement assay by challenging constant amounts of MIP-1427 with a varying concentration of non-radioactive Sc( iii ) complex. Non-radioactive DCFPyL was employed as an assay standard and to calculate relative K i 's based on the obtained IC 50 values.…”
Section: Resultsmentioning
confidence: 99%
“…In order to determine the binding affinity of both conjugates, we carried out the chemical synthesis of MIP-1427, a 99m Tc-radiolabeled, well-established PSMA-targeting imaging probe which has already been evaluated in patients. 32 , 50 Following successful synthesis, we carried out a radioactive displacement assay by challenging constant amounts of MIP-1427 with a varying concentration of non-radioactive Sc( iii ) complex. Non-radioactive DCFPyL was employed as an assay standard and to calculate relative K i 's based on the obtained IC 50 values.…”
Section: Resultsmentioning
confidence: 99%
“…Although positron emitting radio nuclides labeling PSMA are widely used in the diagnosis and treatment of prostate cancer, Tc‐99m remains the radionuclide of choice for clinical scintigraphic imaging due to its favorable physical properties, low cost, and widespread availability . In addition, the radiation exposure from a single administration of a diagnostic dose is approximately 0.0046 mSv/MBq — similar to the radiation exposure from a conventional bone scan in nuclear imaging.…”
Section: Discussionmentioning
confidence: 99%
“…SPECT/CT with PSMA ligand 99m Tc-MIP-1427 was compared to conventional bone scans by Rathke et al in 21 patients with metastatic disease. The study showed an advantage for PSMA SPECT/CT, mainly by decreasing the number of equivocal findings and by its higher specificity, as it does not readily accumulate in degenerative bone disease ( 71 ).…”
Section: Spect Psmamentioning
confidence: 98%